Patient Reported Outcomes (PROs) – a Tool for Strengthening Patient Involvement and Measuring Outcome in Orthopaedic Outpatient Rehabilitation - Müller, Marcus; Brunssen, Joscha; Messingschlager, Martin (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
The present study serves to establish Patient Reported Outcomes (PROs) as a tool for strengthening patient involvement and measuring outcomes in orthopaedic outpatient rehabilitation. Assessments by FFbH-R (Hannover Back Function Questionnaire for patients with back problems), Quick-DASH (Disabilities of Arm, Shoulder, and Hand Score for patients with upper extremity lesions), and LEFS (Lower Extremity Function Scale for patients with lower extremity lesions) were employed in 20 outpatient rehabilitation centres over a period of 12 months to evaluate changes in performance and participation from the subjective patient perspective. The following questionnaires were used: FFbH-R status post: lumbar disc surgery; cervical disc surgery; spinal canal decompression; conservative back pain treatment; other; Quick-DASH status post: rotator cuff reconstruction; shoulder arthroplasty; fracture (conservative or osteosynthesis); other; LEFS status post: hip arthroplasty; knee arthroplasty; anterior cruciate ligament repair; osteotomy; fracture (conservative treatment or osteosynthesis); other. Analysis of the 6,751 usable data sets demonstrated significant positive changes in all scores and diagnostic subgroups. The mean difference in score was 14.2 points in the FFbH-R, − 22 points in the Quick-DASH and 18 points in the LEFS. Thus, this study proves the positive effects of orthopaedic rehabilitation in an outpatient setting. PROs were instituted on a permanent basis in seven of the participating institutions.Die vorliegende Studie dient der Etablierung von Patient Reported Outcomes (PROs) zur Stärkung der Patientenselbstbeteiligung und Ergebnismessung in der ambulanten orthopädischen Rehabilitation. In 20 ambulanten Rehabilitationszentren wurden die Assessments Funktionsfragebogen-Hannover-Rücken (FFbH-R, Rückenpatienten), die Kurzform des Disabilities of Arm, Shoulder Hand and Score (Quick-DASH, Patienten mit Läsionen der oberen Extremitäten) und die Lower Extremity Function Scale (LEFS, Patienten mit Läsionen der unteren Extremitäten) über einen Zeitraum von 12 Monaten verwendet, um die Veränderungen der Leistungsfähigkeit und Teilhabe aus subjektiver Patientensicht zu erfragen. Unterschieden wurde nach: FFbH-R: lumbale Bandscheiben-OP, zervikale Bandscheiben-OP, Spinalkanaldekompression, konservative Rückenschmerzbehandlung, sonstige; Quick-DASH: Rotatorenmanschettenrekonstruktion, Schultergelenkendoprothese, Fraktur (konservativ oder osteosynthetisch versorgt), sonstige; LEFS: Hüftgelenkendoprothese, Kniegelenkendoprothese, vordere Kreuzbandplastik, Osteotomie, Fraktur (konservativ oder osteosynthetisch versorgt), sonstige. Bei insgesamt 6751 verwertbaren Datensätzen wurden für alle Scores und Diagnosesubgruppen signifikant positive Veränderungen nachgewiesen. Die mittlere Scoredifferenz betrug beim FFbH-R 14,2 Punkte, − 22 Punkte für den Quick-DASH und 18 Punkte für LEFS. Damit zeigt diese Untersuchung positive Effekte orthopädischer Rehabilitation im ambulanten Setting. In 7 der teilnehmenden Einrichtungen konnten PROs dauerhaft etabliert werden.
Keywords: rehabilitation; outpatient; orthopedics; patient involvement; Patient Reported Outcome